Improving Students' Vocabulary Mastery through a Game-Based Learning Model Assisted by the Brain Battle Game in Class XI.2 of SMA N 3 Amlapura, Academic Year 2025/2026 - I Ketut Jemen Diantara; I Ketut Wiriawan; Nur Ilmi Wathoni (Green Publisher Indonesia, 2026)
This classroom action research aimed to improve students’ vocabulary mastery through the implementation of a Game-Based Learning model assisted by the Brain Battle Game in Class XI.2 of SMA N 3 Amlapura during the 2025/2026 academic year. The research subjects consisted of 35 students, including 17 male students and 18 female students. The study was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. Data were collected using vocabulary tests, observation sheets, questionnaires, and documentation. The findings showed that the implementation of the Game-Based Learning model assisted by the Brain Battle Game significantly improved students’ vocabulary mastery. In the pre-test, the students’ average score was 59.43, and only 22.86% of students achieved the Minimum Mastery Criterion (Kriteria Ketuntasan Minimal or KKM). After the implementation of Cycle I, students demonstrated improvements in vocabulary comprehension, participation, and motivation during the learning process. The use of interactive games, competition, and immediate feedback increased students’ enthusiasm for learning English vocabulary. In Cycle II, students became more active, confident, and collaborative during classroom activities. Their vocabulary mastery improved in terms of word meaning, spelling, pronunciation, and word usage. Based on these findings, it was concluded that the Game-Based Learning model assisted by the Brain Battle Game was effective in improving students’ vocabulary mastery. Furthermore, this approach created a more enjoyable, interactive, and motivating learning environment in English language learning.